Saddled with murder - Brady, Eileen (Veterinarian) (Brady, Eileen (Veterinarian). Dr. Kate vet mystery., 2020)
"Dr. Kate already has a full plate, juggling clinic visits and house calls on behalf of the Oak Falls Animal Hospital, as well as her--two!--boyfriends. But when she hears that her long-estranged father has invited her and her grandfather to spend Christmas with him and his 'replacement' family, she doesn't think things can get any worse. Then a video taken by a coworker at the holiday office party is posted on social media. In it, Kate proclaims her secret selfish holiday wish--that her two problem clients would disappear. Other staff members had yelled out the names, but that doesn't make Kate feel any less guilty when she finds the corpse of Frank Martindale during a house call the next morning. But when the second problem client turns up dead of hypothermia after a fall at her own home, the video goes viral, and Kate gets a whole lot of attention she hadn't bargained for"--Page 4 of cover.